Nanocrystal Technology as a Tool for Improving Dissolution of Poorly Soluble Drugs - Manar Adnan Tamer (Journal of Global Pharma Technology, 2016)
Many approaches have been developed over time to counter the bioavailability limitations of poorly soluble drugs. With advances in nanotechnology in recent decades, this issue has been approached through the formulation of drugs as nanocrystals. Nanocrystals consist of pure drug(s) and a minimum of surface active agent(s) required for stabilization. They are carrier-free submicron colloidal drug delivery systems with a mean particle size typically in the range of 200 - 500 nm. By reducing particle size to nanoscale, the surface area available for dissolution is increased, and thus bioavailability is enhanced. Drug nanocrystals constitute a versatile formulation approach to enhance the pharmacokinetic and pharmacodynamic properties of poorly soluble drugs. This enhancement is achieved by increasing the dissolution velocity, saturation solubility and mucoadhesion. However, stabilization of nanocrystals remains a major challenge in the development of nanocrystals. Main stability issues include increase in particle size, agglomeration, crystal transformation, and chemical instabilities. as such, combination of steric and ionic stabilizers are required for optimal stabilization. Nanocrystals can be administered by various routes including oral, parenteral, ocular, pulmonary and dermal routes with enhanced pharmacodynamic activity and safety. Functionalization of nanocrystals with radionuclide, imaging moieties and ligands further increases the versatility of nanocrystals. Nanocrystals has been proven successful, as demonstrated by the number of marketed drug products utilizing this technology. The present work provides an overview of the more recent achievements in improving the bioavailability of poorly soluble drugs according to their administration route, and describes the methods developed to overcome physicochemical and stability related problems.Keywords: Nanocrystals, Poorly soluble drug, Nanotechnology.